supondo v=N resolva as equações
Anexos:
![](https://pt-static.z-dn.net/files/d84/6c185784ac1ff4089670f62f7da2b94b.jpg)
Soluções para a tarefa
Respondido por
1
5x - (x - (x - 1)) = x + 3
5x - (x -x +1) = x + 3 Trocar o sinal dos números que estão dentro dos parênteses.
5x - ( 0 + 1) = x + 3
5x - 1 = x + 3
5x - x = 3 + 1
4x = 4
x = 4/4 = 1
5x - (x -x +1) = x + 3 Trocar o sinal dos números que estão dentro dos parênteses.
5x - ( 0 + 1) = x + 3
5x - 1 = x + 3
5x - x = 3 + 1
4x = 4
x = 4/4 = 1
Perguntas interessantes
Português,
11 meses atrás
Matemática,
11 meses atrás
Física,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás
Geografia,
1 ano atrás